MRI features in dengue encephalitis: A case series in South Indian tertiary care hospital - Soni, Brijesh K (Indian J Radiol Imaging, 2017)
Dengue virus, a RNA virus of family Flaviviradae is considered non-neurotropic. Increasing studies and case reports reveal neurological manifestations of dengue virus. In our case series, we have evaluated magnetic resonance imaging (MRI) findings of 3 patients with dengue fever diagnosed by positive dengue NS1 antigen with neurological symptoms, which revealed nonspecific imaging features of dengue encephalitis in two cases and dengue meningoencephalitis in one case. Autopsy findings are also correlated in 2 patients who succumbed to their disease. This case series underlines the consideration of dengue encephalitis in patients of dengue fever with neurological symptoms and relevant imaging findings.